Foreign exchange market pressure - Central Bank of Nigeria, Research Department (Abuja, Nigeria Central Bank of Nigeria, 2016)
Focuses on exchange market pressure with the objective of explaining concepts on the subject matter in relation to developments in exchange rate movement in the foreign exchange market that has implications for the management of the economy.
Includes bibliographical references.
oif 30/05/17
Ref.
Keywords: Foreign Exchange